Application of Fourier plane imaging to LIDAR technologies - Dinesh s/o Kannan (Nanyang Technological University, 2023)
The push to automate our daily lives has introduced an exponential increase in the development of new and old technologies to help us achieve these goals. One of these technologies, 3D imaging, has been rapidly evolving to allow automation hardware today to be able to sense their surrounding environments more precisely, and quickly. The emergence of Light Detection and Ranging (LIDAR) as a 3D technology in many of our everyday objects, including but not limited to, drones, self-driving cars, household appliances, advanced medical and industrial technologies require us to formulate a testing method for up-and-coming systems today. Some of todays’ LIDAR architectures and systems are presented, and our focus on the frequency-modulated continuous wave (FMCW) LIDAR system is our focus for this report. By using Fourier Plane Imaging techniques, we enable the reconstruction of high-resolution images of certain photonic structures for the analysis of the sample’s efficiency and angled information, which allows us to read into the effectiveness of future LIDAR systems which employ the use of quantum photonics.